1998
DOI: 10.1128/jcm.36.3.657-661.1998
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Clinical Laboratory Comparison of Two Supplemented Aerobic and Anaerobic Media Used in Automated Blood Culture Systems To Detect Bloodstream Infections

Abstract: A 20-ml blood sample was collected from adult patients with suspected bloodstream infections and distributed equally into the four volume-controlled bottles of a blood culture set consisting of aerobic and anaerobic BACTEC Plus/F bottles and aerobic and anaerobic BacT/Alert FAN bottles. All bottles were incubated in their respective instruments for a standard 5-day protocol or until the instruments signalled positivity. Samples in all bottles with negative results by these instruments were terminally subcultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
28
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(32 citation statements)
references
References 18 publications
3
28
0
1
Order By: Relevance
“…Many different blood culture systems are in use for the detection of microorganisms in human blood or body fluids. Others tested the blood culture systems used in our study and found comparable abilities of recovering aerobic and anaerobic organ‐isms 20‐22 . Therefore, we believe that the blood culture systems used in our study does not contribute to the differences in contamination rate.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Many different blood culture systems are in use for the detection of microorganisms in human blood or body fluids. Others tested the blood culture systems used in our study and found comparable abilities of recovering aerobic and anaerobic organ‐isms 20‐22 . Therefore, we believe that the blood culture systems used in our study does not contribute to the differences in contamination rate.…”
Section: Discussionsupporting
confidence: 52%
“…Nevertheless, the volume of material inoculated in the blood culture bottles might influence the detection rate 20 . Weinstein and colleagues, 23 who performed a study to evaluate 5 versus 10 mL of blood cultured in aerobic BacT/Alert blood culture bottles, found a significant increase in the yield and speed of detection of blood pathogens 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, in a comparative study between the BACTEC 9240 (Becton Dickinson, Heidelberg, Germany) and the BacT/ Alert system, Ziegler et al reported 9 versus 14 false-negative blood cultures, respectively (8). Although the overall falsenegative rate for the BacT/Alert was only 0.32% in that study, more than 64% of the false-negative cultures were P. aeruginosa, Acinetobacter spp., and S. maltophilia.…”
Section: Discussionmentioning
confidence: 92%
“…In response to these demands, the development of continuously monitoring blood culture systems took place. The BacT/ Alert system (Organon Teknika, Eppelheim, Germany) is one of the fully automated blood culture systems (8). The BacT/ Alert software examines the readings from each bottle to determine if there is evidence for bacterial growth.…”
mentioning
confidence: 99%
See 1 more Smart Citation